Sistem Pakar Pemilihan Minat Program Studi Menggunakan Metode Forward Chaining - Muhammad Andre Syihab (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The choice of a college study program makes students confused, because they do not understand their own potential so that it makes them think they are afraid to choose the wrong major in a study program. In fact, the decision made in choosing a study program becomes a problem, starting from following friends or on the basis of coercion from parents. The choice of study program must really be considered and adjusted so as not to be a regret in the future. Therefore an expert system was created to make it easier for students who want to choose a college study program. The method used is the Forward Chaining method to determine the study program solutions that must be taken. This expert system process accepts options that are already available and have been filled in by students. The results of this expert system provide a solution for selecting study programs based on previous school education.